2014
DOI: 10.1073/pnas.1402012111
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenicity of hypoxic respiring cancer cells revealed by a hypoxia–cell cycle dual reporter

Abstract: Although aerobic glycolysis provides an advantage in the hypoxic tumor microenvironment, some cancer cells can also respire via oxidative phosphorylation. These respiring ("non-Warburg") cells were previously thought not to play a key role in tumorigenesis and thus fell from favor in the literature. We sought to determine whether subpopulations of hypoxic cancer cells have different metabolic phenotypes and gene-expression profiles that could influence tumorigenicity and therapeutic response, and we therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 29 publications
0
48
2
Order By: Relevance
“…However, it is clear that tumor heterogeneity should be taken into consideration for proper interpretation. Recent studies indicate metabolic heterogeneity among hypoxic cancer cells, and that hypoxic tumor cells contain a sub-population of non-Warburg respiring cells [43]. Previously, we have shown that Mito-CP and other mitochondria-targeted antioxidants inhibit Nox2 expression and activity in mice and inhibit nitration and carbonylation of proteins induced by NADPH oxidases (Nox) and inducible NOS [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that tumor heterogeneity should be taken into consideration for proper interpretation. Recent studies indicate metabolic heterogeneity among hypoxic cancer cells, and that hypoxic tumor cells contain a sub-population of non-Warburg respiring cells [43]. Previously, we have shown that Mito-CP and other mitochondria-targeted antioxidants inhibit Nox2 expression and activity in mice and inhibit nitration and carbonylation of proteins induced by NADPH oxidases (Nox) and inducible NOS [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Transduced cells were selected with 1 μg/mL puromycin and observed by fluorescence microscopy to detect the cycling cell subpopulation (mCherry + ). Cells were then exposed to 1% O 2 overnight for hypoxia assessment (GFP + ) after 0, 2, 4, 8, and 24 h of reoxygenation (21). To generate orthotopic tumors, 5 × 10 6 cells from each HypoxCR-pancreatic cancer cell line in 50 μL PBS and Matrigel in a 1:1 ratio were injected into the pancreas.…”
Section: Methodsmentioning
confidence: 99%
“…Although the efficacy of BPTES-NPs in mice was found to be similar to CB-839, BPTES-NPs were better-tolerated, showing no liver toxicity, in contrast to CB-839-treated mice. In vivo imaging using the HypoxCR reporter (21) revealed that BPTES-NPs targeted the replicating tumor cell subpopulation without affecting hypoxic cells. Using NMR and liquid chromatography-mass spectrometry (LC-MS), we found that the residual tumor cells after BPTES-NP treatment were reliant on glycolysis and glycogen synthesis.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…HIF1-a-induced expression of pyruvate dehydrogenase kinases (PDKs) decreases oxidative metabolism of glucose, while glycolytic targets of HIF1-a stimulate lactate generation. However, non-HIF-1a-expressing cells can maintain higher respiration rates under hypoxic conditions [88], of potential relevance to naïve ES cells, which exhibit low HIF-1a expression and a HIF-inducible shift to EpiSC phenotype [21 ].…”
Section: Stem Cell Nichesmentioning
confidence: 99%